GYMNASTICS IS THE SOURCE OF HEALTH (Conferencea, 2022)
Today, due to the high attention paid to sports by the leadership of our government, the achievements of our country's female athletes in the world arenas are enormous. Because of independence, we had a lot of opportunities. It is both an obligation and a duty for us to act accordingly, to increase our achievements in all spheres. Due to the care of the President of the Republic of Uzbekistan for women, the attitude to the sport of rhythmic gymnastics, which is one of the important factors in restoring, strengthening and protecting their health, has changed radically during the years of independence. After all, sport is an ambassador of solidarity, friendship, goodness, a symbol of maturity.